Short-term intermittent prophylaxis post-intracranial hemorrhage in children with hemophilia - Novie Amelia Chozie; Fitri Primacakti; Made Citra Saraswati; Damayanti Sekarsari (Paediatrica Indonesiana, 2022)
Background Intracranial hemorrhage (ICH) is one of the major bleeding events causing mortality and long-term morbidity in children with hemophilia, especially those who receive on-demand therapy. Objective To evaluate the outcome of children with hemophilia after ICH receiving short-term intermittent prophylactic treatment. Methods This retrospective study was conducted in the Department of Child Health, Dr. Cipto Mangunkusumo Hospital, Jakarta. Children £18 years of age with hemophilia presenting with ICH between 2015-2020 were included. We recorded patients’ demographics, type and severity of hemophilia, the presence of factor VIII (FVIII) inhibitor, brain CT scan, treatment, and outcomes of these patients. Patients who received short-term intermittent prophylaxis using clotting factor concentrate (CFC) post-ICH episodes were observed for ICH recurrence. Results There were 19 episodes of ICH experienced by 18 patients, consisting of 16 patients with hemophilia A and 2 with hemophilia B. Patients’ median age was 4 years (range 0-16 years). Hemophilia was classified as severe in 13 patients, moderate in 4 patients, and mild in 1 patient. Thirteen episodes were preceded by head trauma. The most common clinical manifestation was seizures (13.2%). The most common type of ICH was subdural hematoma. Two patients died and 2 patients had neurological sequelae during hospitalization. The median dose of short-term intermittent prophylaxis using CFC (n=16) was 20 IU/kg of FVIII twice a week and 30 IU/kg of FIX twice a week, for a median duration of 8 weeks (range 5-12 weeks). One patient who did not adhere to the prophylaxis regimen had recurrent ICH at a similar location 6 months after the first episode. Conclusion Our findings suggest that short-term intermittent prophylaxis is important to prevent the recurrence of ICH in children with hemophilia.